A multi-locus phylogeny of Euryops (Asteraceae, Senecioneae) augments support for the "Cape to Cairo" hypothesis of floral migrations in Africa - Devos, N.; Barker, N.; Nordenstam, B.; Mucina, Ladislav (International Association for Plant Taxonomy, 2010)
With about 100 species, Euryops (Cass.) Cass. ranks among the most speciose genera of the tribe Senecioneae (Asteraceae). The genus has its greatest diversity in South Africa, and displays an interesting disjunct distribution with most of the taxa found in southern Africa and a group of eight endemic species confined to the mountains of tropical East Africa and northeastern Africa. Molecular phylogenetic analyses of DNA sequence data from three chloroplast fragments and the nuclear ITS region were used to reconstruct the evolutionary history of 41 Euryops species in order to unravel species relationships and to determine the origin of the disjunct Afromontane taxa. Our results show a lack of support and resolution in the internal structure of the trees, but also reveal strong incongruence between the ITS and cpDNA datasets as assessed by Bayes Factors. We hypothesise that this is a consequence of the isolation and divergence of many populations over a short time period at some point in the history of the genus. Molecular dating based on our phylogenetic tree suggests that the genus diversified in South Africa around four million years ago. The origin of the East African species, dated at 1.9 Ma, well after the uplift of the East African mountains, is consistent with a scenario of a single dispersal event from South Africa northwards into the tropical East African mountains where diversification occurred, creating a monophyletic group of regional Afromontane endemics.